Pendekatan Ekonomi Sirkular Dalam Industri Tembakau : Mendaur Ulang Limbah WWTP Menjadi Kompos Kaya Nutrisi Melalui Proses Anaerobik - Tri Figur Fuad; Abdul Wahid (Jurnal Serambi Engineering, 2025)
The implementation of circular economy principles is crucial for industries to achieve sustainability, including the tobacco industry which generates significant organic waste in the form of sludge from its Wastewater Treatment Plant (WWTP). This study demonstrates a circular economy model by upcycling WWTP sludge into nutrient-rich compost using anaerobic digestion (AD) technology. The AD process was conducted on the sludge at a laboratory scale under mesophilic temperature conditions. The quality of the final compost product (digestate) was evaluated based on physicochemical parameters and compared with national compost quality standards. The results showed that the AD process successfully transformed the sludge into a stable and nutrient-rich material. The final product's C/N ratio reached 20:1, which is ideal for soil application. The contents of total N (1.6%), Phosphorus (P₂O₅ 1.1%), and Potassium (K₂O 0.9%) indicate its potential as an effective organic fertilizer. The quality of the compost produced was proven to meet the SNI 19-7030-2004 quality standard. This study confirms that upcycling sludge via AD is a feasible and effective approach to implementing a circular economy in the tobacco industry, turning a waste burden into a valuable product and supporting sustainable agriculture.